2019
DOI: 10.2478/s11686-019-00152-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Seroprevalences of Rickettsia conorii, Ehrlichia canis and Coxiella burnetii in Dogs from Montenegro

Abstract: Due to an unfortunate error during the processing of the article, the given name and family name of all authors were interchanged. The original article has been corrected. Publisher's Note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recent study in Montenegro found antibodies to C. burnetii in three dogs (1.2%), two from the public dog shelter and one from the coastal area. This low seroprevalence has been explained by the fact that Q fever was not endemic or enzootic in the investigated area [9].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A recent study in Montenegro found antibodies to C. burnetii in three dogs (1.2%), two from the public dog shelter and one from the coastal area. This low seroprevalence has been explained by the fact that Q fever was not endemic or enzootic in the investigated area [9].…”
Section: Discussionmentioning
confidence: 89%
“…burnetii-infected dogs and cats can develop asymptomatic forms, and pregnant females may have abortions as well. DNA of the agent was found in different canine specimens, suggesting that dogs may be a source of infections for their owners and other animals [8,9].…”
Section: Introductionmentioning
confidence: 99%